Nutrient restriction synergizes with retinoic acid to induce mammalian meiotic initiation in vitro - Xiaoyu Zhang (Nature Portfolio, 2021)
Retinoic acid is necessary but not sufficient to induce meiosis. Here, the authors use primary mouse undifferentiated spermatogonia culture to show that nutrient restriction, an inducer of yeast meiosis, combined with retinoic acid induces meiotic gene and chromosome programs in mammalian germ cells.